THE USE OF PEER EDITING TO IMPROVE STUDENTS’ SKILL IN WRITING DESCRIPTIVE PARAGRAPH AT SMP NEGERI 3 TONDANO - Parimalang, Farhan Ryan; Maru, Mister Gidion; Lambe, Livianni (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
The aim of this study was to find out whether peer editing improved students' skill in writing descriptive paragraph. This research used quantitative research methods through pre-experimental design. The type of test that was used was a written test. Students were asked to write descriptive paragraphs about describing people. The subject of the study was one of the classes in the seventh grade of SMP Negeri 3 Tondano with a sample of 25 students. The students’ scores were evaluated by two inter-raters, and the data were statistically analyzed using SPSS software. The results of the normality test showed that the data were normally distributed. The average pre-test score was 52.32, while the average post-test score increased to 69.80, indicating that peer editing was able to provide a significant impact on students' ability to write descriptive paragraph. Meanwhile, the results of the paired sample t-test analysis also revealed a significant difference between the pre-test and post-test scores, with a significance value (p-value) < 0.001, which was lower than the alpha level (α = 0.05); therefore, H₀ was rejected and Hₐ was accepted. that peer editing was effective in improving students’ skills in writing. Based on the findings, it could be concluded that peer editing was effective in improving students’ skills in writing descriptive paragraphs at SMP Negeri 3 Tondano. The implication of this study is that English teachers can apply peer editing as an effective technique to improve students’ writing skills, especially in writing descriptive paragraphs.